2011
DOI: 10.1162/rest_a_00140
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Consumption at Retirement: Evidence from Panel Data

Abstract: Previous empirical literature has found a sharp decline in consumption during the first years of retirement, implying that individuals do not save enough for their retirement. This phenomenon is called the retirement consumption puzzle. We find no evidence of the retirement consumption puzzle using panel data from 1980 to 2000. Consumption is defined as nondurable expenditure, a more comprehensive measure than only food used in many of the previous studies. We find that food expenditure declines at retirement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 22 publications
8
58
2
Order By: Relevance
“…In contrast to some of the earlier studies which found significant reductions in food expenditures at the time of retirement, recent literature has looked at broader consumption measures than just food expenditures and found, consistent with the standard life-cycle model, no significant consumption drop (see, e.g., Fisher et al (2008), Aguila et al (2011)). For the great majority of households, expenditures on food constitute a relatively small share of household budgets, and the relevance of changes in specific expenditure components for testing the life-cycle model seems questionable.…”
Section: Introductionmentioning
confidence: 74%
“…In contrast to some of the earlier studies which found significant reductions in food expenditures at the time of retirement, recent literature has looked at broader consumption measures than just food expenditures and found, consistent with the standard life-cycle model, no significant consumption drop (see, e.g., Fisher et al (2008), Aguila et al (2011)). For the great majority of households, expenditures on food constitute a relatively small share of household budgets, and the relevance of changes in specific expenditure components for testing the life-cycle model seems questionable.…”
Section: Introductionmentioning
confidence: 74%
“…First and perhaps most fundamentally, Aguila, Attanasio, and Meghir (2011) do not find any expenditure drop after retirement at all for non-durable consumption goods, using micro panel data for the US. A very similar result for German expenditure survey data was found by Beznoska and Steiner (2012).…”
Section: Introductionmentioning
confidence: 76%
“…In addition, recently Li, Shi, and Wu (2015) explore expenditure changes at retirement in China using the UHS data. 3 Unlike the existing studies, we focus on separating price changes from quantity changes at retirement when retirement is fully anticipated. We also investigate how food-shopping time changes.…”
Section: Relationship To Existing Studiesmentioning
confidence: 99%